Corn Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Thompson, Curtis R.; Stockton, Roger (My University, 2001)
This publication provides estimated cost and returns for forward farm planning for corn in western Kansas.
MF2150_2001_10
Keywords: MF2150; Crops; Economics; MF